The Effect of Unemployment, Education, and Population Size on Poverty Levels in the Province of NTB From 2019 to 2023 - Nandini Putri, I Gusti Ayu Agung (West Science Social and Humanities Studies, 2025)
This study aims to determine the effect of unemployment rate, education level and population on poverty rate in NTB Province in 2019-2023. In this study, data collection was carried out directly through BPS NTB Province. By using poverty rate data, namely data on the percentage of the number of poor people, unemployment rate data, namely data on the percentage of open unemployment rates, education level data, namely data on the average length of schooling, and data on the total population of NTB Province in 2019-2023. The panel data analysis method in this study is multiple linear regression analysis using Eviews12. The results of this study indicate that the unemployment rate has a negative and insignificant effect on the poverty rate, the education level has a positive and significant effect on the poverty rate, and the population also has a negative and significant effect on the poverty rate. Simultaneously, the unemployment rate, education level and population have a significant effect on the poverty rate in NTB province in 2019-2023.